Pengaruh Model Problem Based Learning (PBL) Terhadap Kemampuan Pemecahan Masalah Biologi Siswa Kelas VIII SMP Negeri 19 Palu - Aiman, Popi Umu; Lilies, Lilies; Sabran, Moh; Astija, Astija; Mawaddah, Hayyatun; Laenggeng, Abd Hakim (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the effect of Problem Based Learning (PBL) learning model on students' biology problem solving skills in class VIII SMP Negeri 19 Palu. The method used was a quasi-experiment with Non equivalent (Pretest and Posttest) Control Group Design. The research sample amounted to 46 students, consisting of 23 experimental class students who used the PBL model and 23 control class students who used the conventional learning model. Data were collected through observation, teacher and student activity assessment sheets, and tests in the form of valid and reliable description questions. Data analysis was carried out with prerequisite tests, namely normality test and homogeneity test, as well as hypothesis testing using Independent Sample t-test. The results showed that there was a significant effect of PBL model on students' biological problem solving ability. The average posttest score of the experimental class reached 91.73, while the control class was only 75.21. The t-test shows a p value <0.05, which means that the alternative hypothesis is accepted, indicating that the application of the PBL model has a positive effect. Thus, it can be concluded that the PBL model is effective and influential on students' biology problem solving skills in science subjects of class VIII-D SMP Negeri 19 Palu.